Transformasi UMKM Tempe melalui Integrasi Penguatan Manajemen, Digitalisasi Usaha, dan Legalitas Berbasis Pendekatan ABCD di Kawasan Sanan - Rizky Fahmi Saputra; Muhammad Naufal Aulia Maulana; Agung Winarno; Wening Patmi Rahayu (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
This community service program aims to transform the management of tempeh MSMEs in the Sanan area through the integration of management strengthening, business digitalization, and legality based on the Asset-Based Community Development (ABCD) approach. The activities were carried out by combining the ABCD and Participatory Action Research (PAR) approaches through the stages of discovery, dream, design, and destiny, involving the active participation of business actors in every process. This approach emphasizes the utilization of local potential and community assets, enabling MSME actors to develop their businesses independently and sustainably. The results of the program indicate that the implementation of standard operating procedures (SOPs) and cross-training programs improved the consistency of production processes, work efficiency, and workforce flexibility in responding to changing production demands. In addition, the use of social media and business location tagging on digital platforms contributed positively to expanding market access and increasing product visibility. Assistance in copyright registration also strengthened the legality and protection of MSME products. Overall, this activity significantly enhanced the adaptive capacity of MSMEs in facing market dynamics and encouraged more structured, competitive, innovative, and sustainable business management.